2020
DOI: 10.1055/s-0039-3400303
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Clinical Prediction Rule for Venous Thromboembolism in Patients with Acute Leukemia

Abstract: Risk factors for venous thromboembolism in patients with solid tumors are well studied; however, studies in patients with acute leukemia are lacking. We conducted a retrospective cohort study of adult patients diagnosed with acute myeloid leukemia and acute lymphoblastic leukemia diagnosed between June 2006 and June 2017 at a tertiary care center in Canada. Potential predictors of venous thromboembolism were evaluated using logistic regression and a risk score was derived based on weighed variables and compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 38 publications
2
29
1
Order By: Relevance
“…In acute leukaemia, Al-Ani et al developed a simple predictive tool that may be used as standard of care but is awaiting ongoing external validation. 49 Despite the availability of different disease-specific scores in lymphoma-related thrombosis, in multiple myeloma, both SAVED and IMPEDED VTE scores performed better than currently used guidelines and can be used in risk stratification of patients with MM. 61,72 The guidelines already recommend the thromboprophylaxis of high-risk patients, given the significant reduction in mortality and morbidity.…”
Section: Conclusion and Practice Pointsmentioning
confidence: 97%
See 3 more Smart Citations
“…In acute leukaemia, Al-Ani et al developed a simple predictive tool that may be used as standard of care but is awaiting ongoing external validation. 49 Despite the availability of different disease-specific scores in lymphoma-related thrombosis, in multiple myeloma, both SAVED and IMPEDED VTE scores performed better than currently used guidelines and can be used in risk stratification of patients with MM. 61,72 The guidelines already recommend the thromboprophylaxis of high-risk patients, given the significant reduction in mortality and morbidity.…”
Section: Conclusion and Practice Pointsmentioning
confidence: 97%
“…A misconception that thrombosis risk in patients with leukaemia was lower than that of solid tumours 48 is being replaced by recent studies which showed the incidence of thrombosis to be similar or even higher than in those with solid tumours. 49 The prevalence of thrombosis in acute myelocytic leukemia (AML) varies. In a cohort of 5394 cases, the largest cohort of AML, the 2-year cumulative incidence of deep vein thrombosis and/or pulmonary embolism was 5.2%.…”
Section: Acute Leukaemiamentioning
confidence: 99%
See 2 more Smart Citations
“…It also opens ways to further important trials assessing thromboprophylaxis in high‐risk patients with other haematological malignancies. Specific VTE risk assessment models have already been developed for acute leukaemia (Al‐Ani risk score), myeloproliferative diseases (IPSET‐thrombosis), or lymphoma (ThroLy score) 10–12 . However, to date, only one randomised pilot trial assessing a DOAC for thrombosis prevention in adult patients with malignant haematologic conditions has been registered with http://ClinicalTrials.gov.…”
mentioning
confidence: 99%